2021
DOI: 10.1007/s12540-020-00957-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Low-Temperature Austempering on the Microstructure and Abrasive Wear of Medium-Carbon Low-Alloy Steel

Abstract: Nano-bainitic steels have attracted great attention for good wear resistance. In this research, a medium-carbon low-alloyed steel was austempered at a low temperature close to its martensite-start temperature for various times to obtain mixed microstructure of nano-bainite, martensite and retained austenite. The austempered samples were characterised comprehensively by field-emission SEM and quantitative XRD. Its two-body abrasive wear property was evaluated by sliding on a SiC abrasive disc. The results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Hal tersebut sejalan dengan pembentukan mikrostruktur pada temperatur austempering yang relatif rendah maka fasa yang terbentuk didominasi martensit yang keras pada matriks ferrit. Di sisi lain, pada temperatur austempering yang tinggi memiliki kecenderungan untuk membentuk fasa pearlite yang dapat memiliki nilai kekerasan relatif rendah [10].…”
Section: Analisis Uji Kekerasanunclassified
“…Hal tersebut sejalan dengan pembentukan mikrostruktur pada temperatur austempering yang relatif rendah maka fasa yang terbentuk didominasi martensit yang keras pada matriks ferrit. Di sisi lain, pada temperatur austempering yang tinggi memiliki kecenderungan untuk membentuk fasa pearlite yang dapat memiliki nilai kekerasan relatif rendah [10].…”
Section: Analisis Uji Kekerasanunclassified
“…In order to get a more precise microstructure, bainite is better formed at lower temperatures (250-300 °C) and for shorter durations [6]. This enhancement over standard quenching and tempering enhances hardness, wear resistance, and corrosion resistance [2,7]. Luo et al [8] also showed that austenitizing for up to 4 hours was enough to move enough carbon from bainitic ferrite to austenite, which made the balance between strength and ductility better.…”
Section: Introductionmentioning
confidence: 99%